Penerapan Metode Modifikasi Perilaku Pembentukan (Shaping) Untuk Membentuk Perilaku Sosial Anak Dengan Ketidak-Mampuan Intelektual Ringan - Gerry Olvina Faz (Jurnal Psikologi Tabularasa, 2015)
Mild intellectually disabled children often experience problems in their social behaviors.On the other side, most of them need assistance from nearby people in order to deal with daily problems.This program, therefore, aims at establishing new social behavior with the shaping technique in modified behavior. The program employs single case with subject having characteristics as follow: female, 11 year old, and diagnosed with mid-intellectual disability. New behavior expectedly to be established is to ask stranger for help in crossing the street with the program held in seven sessions. During the process, positive reinforcement, fading and generalization were also given. The program results in subject able to show behavior of asking stranger for help in order to help her cross the street through the shaping technique in modified behavior.